Discovery learning with hierarchy concept to improve analysis ability and study achievement hydrolysis subject - Leny Yuliatun; Mohammad Masykuri; Budi Utami (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2017)
The aim of this research is to applied Discovery Learning (DL) by the support of hierarchy concept to improve analysis ability and chemistry study achievement in the Hydrolysis subject at eleventh-grade students of Science 1 of SMA N Karangpandan at the academic year of 2016/2017. This research is using Classroom Action Research which using two cycles. In each cycle has four steps of action, they are planning, implementing, observing, and reflecting. The research subject is the eleventh-grade students of science one which consists of 40 students. The data source is using teacher and students and the data were taken by interviewing, observing, documenting, testing, and using questionnaire. Data analysis technique is using descriptive qualitative analysis. Based on the research shows that the achievement of analysis cycle I am from 52,5% increase into 65% in the cycle II. Meanwhile, the rise in students’ achievement in cognitive aspect increase from 57,5% in cycle I to 75% in cycle II. Achievement in an affective aspect in cycle I am 90% become 92,5% in cycle II. Therefore, there is the increase meant of students number in this aspect although in cycle I all of the indicator has been reached.